Teachers' reflections of instructional effectiveness: self-assessment through a standards-based appraisal process. Issue 1 (2nd January 2019) - Davis, Amanda; McDonald, Denise
ABSTRACT: This paper explores teachers' reflections on: (1) self-assessment of their own videotaped lesson using a standards-based appraisal system; (2) comparison to an external reviewer's evaluation of the same lesson; and (3) effect of the appraisal system on their pedagogical views, professional development, and actual practice improvement. Findings indicate that teachers view the appraisal system as evaluative with little impact on their teaching practice and professional growth. Participating teachers indicated that the self-evaluative reflection process utilized in the study had a greater influence on their professional development than the appraisal system as it is currently structured.